The CardioOP-Data Clas (CDC) - Friedl, R.; Klas, W.; Westermann, U.; Rose, T.; Tremper, J.; Stracke, S.; Gödje, O.; Hannekum, A.; Preisack, M. B. (Methods of Information in Medicine, 2003)
Objectives: Self-directed and customized medical education programs are gaining importance in health care instruction. We prototypically implemented a repository-driven online computer system (CardioOP) for teleteaching in Heart Surgery. It supports authoring and multiple re-use of multimedia data for different user groups in different instructional applications and therefore requires a process of content management.Methods: We defined objectives for a terminological system to support semantic, cross-media type annotation and retrieval of learning objects: domain completeness, German (natural) language processing, multi-user concepts, extensibility and maintenance, content based annotation and technical implementation. Existing terminologies (ICD10, READ V3, Snomed III, UMLS 1997, MESH) have been analysed according to these objectives.Results: We found that the analysed terminologies did not meet our criteria sufficiently. Therefore, we developed a domain-specific thesaurus, the CardioOPDataClas (CDC). The application of the CDC within a database-driven authoring process using specifically developed tools is reported.Conclusions: Metadata play an important role in the effective discovery and search, access, integration and management of educational multimedia data in medicine but so far, there is no terminology to support content management for instructional multimedia. We prototypically designed and applied a thesaurus for the CardioOP educational system. Additional work is needed to evaluate the system in terms of user-friendliness, concept coverage and information retrieval performance.
Keywords: Computer assisted instruction; multimedia; terminology; information management